Spirituality as Poetry: On Richard Berengarten's Balkan Trilogy - Sneller, Rico (Studies in spirituality, 2019)
In this article the work of the contemporary Jewish-British poet Richard Berengarten (1943) is examined in light of its potential to re-articulate the question of suffering as a prospective experience of beauty. I try to interpret a decisive motif in Berengarten's(themotif) through the backdrop of a possibly more "adequate" account of Being, i.e., an account that attempts to do justice to an inner relation between Being and language. That which for convenience's sake I propose to call a "ontology" can already be found in the ancient mystical, which determined medieval Kabbalah. It re-appeared both in modern philosophy (from Hamann to Heidegger, Gadamer, Derrida) and in modern poetry (Mallarmé etc.) or literature (Joyce).